Farmers’ Perceptual Analysis on Change Dynamics of Effectiveness of Extension Agent in Agriculture (Indian Journal of Extension Education, 2016)
Agricultural extension and advisory services play an important role in addressing the burning challenges of modern agriculture. The present study has delved deeper and also envisaged the perceptual and situational analysis of change dynamics of effectiveness of extension agent by taking 19 independent variables and dependent variable, change in perceived effect of extension agent (Y4) on the basis of decadal observation from 1984 to 2014. The result shows that, the variables like, Change in Watching T.V (X13), Change in Consumption of Kerosene (X6), Changing Interaction with Extension Agent (X15), Change in average fertilizer dose (X19), all have significant correlation and contributed variance to the consequent variable. Result shows that interaction with extension agent and change in fertilizer application, have made a socio-operational diode to estimate change dynamics as recorded by extension agent. Results also found that majority (53.75%) of the respondents had no contact with the extension agents, while 40 per cent were visited rarely (3 – 6 times per year). About 10.23 per cent had contact often or monthly while only 12.5 per cent had contact very often (fortnightly or more) in a year with extension agent which shows the inefficiency of agricultural public extension system.